PUFA and carotenoid producing thraustochytrids and their anti-microbial and antioxidant activities - Kaliyamoorthy, Kalidasan; Chavanich, Suchana; Kandasamy, Kathiresan; Ponnuvel, Mohanchander; Kamlangdee, Niyom; Taoka, Yousuke; Viyakarn, Voranop (Frontiers in Marine Science, 2023)
Thraustochytrids contribute to the microbiota of mangrove ecosystem, and they hold promise as a potential source of polyunsaturated fatty acids (PUFAs), antimicrobials and antioxidants for their application in pharmaceutical, aquaculture, and human health sectors. However, the thraustochytrids have not been properly studied in Indian mangrove ecosystems for their PUFAs and biological activities, and hence, the present study was carried to isolate the PUFAs-rich thraustochytrids for their pigments, antimicrobial and antioxidant properties. This work isolated and identified the thraustochytrids that are capable of producing PUFAs from decomposing leaves of mangroves at Pichavaram, southeast coast of India. Two predominant isolates were identified as Thraustochytrium sp. and Aurantiochytrium mangrovei based on morphological and molecular characteristics. Thraustochytrium sp., produced the biomass of 4.72 g L-1, containing total lipids of 42.36% and docosahexaenoic acid (DHA) of 32.69% of total lipids, whereas, A. mangrovei produced the biomass of 6.25 g L-1 containing total lipids of 49.81% and DHA of 44.71% of total lipids. Astaxanthin pigment accumulated up to 3.2 µg L-1 in A. mangrovei, whereas the pigment was not detected in Thraustochytrium sp. Further, the biomass extracted in organic solvents was tested for antibacterial activity against seven clinical pathogens along with positive control of ampicillin. Thraustochytrium sp., exhibited the highest antibacterial activity with the zone of inhibition of 78.77% against Staphylococcus aureus and the lowest (20.95%) against Klebsiella pneumonia. Thraustochytrium sp., also showed minimum inhibitory concentration (MIC) of 40 µg L-1 inhibiting the growth of S. aureus. The antioxidant activity of A. mangrovei was tested by using six assays and noted the highest free radical scavenging (87.37 ± 1.22%) and the lowest nitric oxide radical scavenging (75.12 ± 2.22%) activities. Hence, it is clear that the extracts of Thraustochytrium sp., and A. mangrovei are promising sources of lead compounds for biopharma and food industries.